Stage-Wise Use of Mass Media in Adoption of BRRI Dhan28 by Farmers of Munshiganj District in Bangladesh - Akter, M; Bhuiyan, M.H.; K.Z. Hossain, K.Z. (Journal of Agricultural Extension Management, 2018)
Mass Media Channels (MMCs) play a significant role in technology diffusion. A major part of technology diffusion is innovation-decision, which consists of some stages. Researchers of transfer of technology have so far conducted studies only on effectiveness of MMCs. Use of MMCs at different stages of innovation–decision process was not focused in-depth. The researchers of the present study undertook research highlighting the objectives of determining and describing the stage-wise use of mass media by the farmers in adoption of BRRI dhan28 and exploring the relationship between stage-wise use of MMCs and their selected characteristics. Data were collected from 90 farmers of five villages of Gazaria Upazila under Munshiganj district of Bangladesh, by using a structured interview schedule. The results demonstrated that 95.5 per cent of the respondent farmers had low to medium use of MMCs, 83.30 per cent had medium to high use, 71.10 per cent had low use, 62.20 per cent had medium and 72.20 per cent had low use of MMCs at knowledge, persuasion, decision, implementation and confirmation stages of innovation-decision process, respectively. Television was found to be highly used in every stage of innovation-decision process followed by radio, leaflet, poster and newspaper. The findings also revealed that age, family size, farm size and annual income of the farmers had significant positive relationship with their use of MMCs at different stages of innovation-decision process. On the other hand, education, organizational participation, cosmopoliteness, innovativeness, attitude towards innovation and problems in using innovation had significant negative relationship. Conclusion could be drawn that in transfer of technology, diffusion agencies should have a clear understanding about ‘preferences of stage-wise use of mass media channels of farmers at various stages of innovation-decision process emphasizing on socio-economic characteristics.’